Pengaruh Keputusan Investasi dan Kebijakan Dividen terhadap Nilai Perusahaan Manufaktur Sektor Konsumsi - Angeline, Viona; Keristin, Usnia Wati (MDP Student Conference, 2024)
The purpose of this research is to examine the influence of investment decisions and dividend policies on the firm's value. This study employs a quantitative approach. The subjects of this research are companies in the non-cylicals sector listed on the Indonesia Stock Exchange during the period 2018 to 2022. Using purposive sampling techniques, a total of 20 companies were selected for examination. Subsequently, data testing applied multiple linear regression analysis. Based on the testing, it was found that investment decisions have a partial effect on firm value, while dividend policy does not have a partial effect on firm value. Simultaneously, investment decisions and dividend policy have an impact on firm value.